Green Customer Behavior: Mediation Model Of Green Purchase - Alamsyah, Doni Purnama; Othman, Norfaridatul Akmaliah; Wan Ibrahim, Nik Rahila; Mulyani, Mulyani; Yogi, Udjaja (Hampstead Psychological Associates, 2020)
This study aims to review the correlation of eco-label on customer behavior, which is green awareness, green trust, and green purchase intention. The study is conducted in Bandung City with a research experimental method to 100 customers of Supermarket Retail who know about a green product. The study is performed by using SmartPLS and path analysis techniques to find the research model. The research result is known that eco-label has a direct correlation to green awareness and green trust, but it does not relate significantly to green purchase intention. It is the same with green awareness that is insignificant can change green purchase intention. It is different from a green trust that can switch directly to green purchase intention. The research finding is stated that customer's green awareness and green trust can genuinely be the correlation mediation of eco-label with green purchase intention. Information from research results provides a positive impact for the company is considering to green customer behavior and government in giving policy to green product development